Menjaga Kesehatan Mental Perspektif Al-Qur’an dan Hadits - Fuad, Ikhwan (Universitas Islam Tribakti Lirboyo Kediri, 2016)
This article elaborates on theories of psychology in the Qur'an and Sunnah on how to maintain mental health. As the basic source of Islam, the Qur'an and the Hadith contains much information and knowledge, including mental health problems amid concern the world of psychology today. With the approach of Normative-theological author tried to dig texts that discuss these topics and explain its theories. The author came to the conclusion that 1) maintaining of mental health in Qur'an and Sunnah perspective based on the notion wasathiyah (moderation) in fulfilling the needs of the material and the spiritual, 2) method of the Qur'an and Hadith in realizing mental health, among others by strengthening the spiritual dimension, control of biological motivations and methods learned are necessary for mental health. Achievement of these methods can be seen from the life of the prophet and the sahabata of the relationship with God, with himself, his relationships with others, and the universe.